Design of a 5.8 GHz directional coupler using electronics design automation tool - Hock G.C.; Chakrabarty C.K. (2023)
This paper describes the quick way to design 5.8 GHz directional coupler by using the latest version of Electronics Design Automation (EDA) tool. The special features from the EDA tool ease the design of the circuitry with the considerations towards cost and time. It also reduces the design latency as faced by designer as many of the design methodology are simplified. In highlighting these prevailing features, 15 dB, 5.8 GHz single layer directional coupler is designed and analyzed. In designing this passive circuit, microstrip lines are implemented 2005 IEEE.